2022
DOI: 10.18178/ijiet.2022.12.2.1601
|View full text |Cite
|
Sign up to set email alerts
|

A Concept Attainment Model Using Cloud-Based Mobile Learning to Enhance the Mathematical Conceptual Knowledge of Undergraduate Students

Abstract: The COVID-19 situation has affected the instructional process, with both students and instructors having to adapt to the conditions that have emerged. The inclusion of online tools as part of teaching and learning is imperative, especially in mathematics courses, in order to provide knowledge and to create a learning environment as close as possible to face-to-face learning. This study focuses on the mathematical conceptual knowledge of undergraduate students using a concept attainment model. This consists of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The results showed that the group of experimental students who learned through mobile learning had a higher creative thinking ability than students who learned through traditional learning media (Mahmudah et al, 2021). Other studies have shown that the use of mobile-based learning media improved students' conceptual knowledge of Mathematics (Anupan & Chimmalee, 2022). The use of mobile technology in the form of both hardware and software integrated into learning activities producedinformation conveyed by teachers for the better because teaching materials can be made more varied with the aim of inspiring student interest in learning, increasing student concentration, enriching curriculum content, and increasing learning comfort (Ateş & Garzón, 2022;Sinaga, Febrianti, & Candra, 2022).…”
Section: Discussionmentioning
confidence: 84%
“…The results showed that the group of experimental students who learned through mobile learning had a higher creative thinking ability than students who learned through traditional learning media (Mahmudah et al, 2021). Other studies have shown that the use of mobile-based learning media improved students' conceptual knowledge of Mathematics (Anupan & Chimmalee, 2022). The use of mobile technology in the form of both hardware and software integrated into learning activities producedinformation conveyed by teachers for the better because teaching materials can be made more varied with the aim of inspiring student interest in learning, increasing student concentration, enriching curriculum content, and increasing learning comfort (Ateş & Garzón, 2022;Sinaga, Febrianti, & Candra, 2022).…”
Section: Discussionmentioning
confidence: 84%
“…The knowledge acquired should be sufficient and relevant to every borderless society, IT society, and competitive society and should improve performance competency and the caliber of information collection and processing. (Anupan & Chimmalee, 2022;Bikanga Ada, 2018;Li et al, 2013;Qiao et al, 2021;Seta et al, 2022;Wang et al, 2021). Pandemic COVID-19 (New Normal) New lifestyles during the COVID-19 pandemic.…”
Section: Digital Transformation In Education Frameworkmentioning
confidence: 99%